Solvothermally synthesized SnS nanorods with high carrier mobility leading to thermoelectric enhancement. Issue 50 (4th May 2016) - Tan, Qing; Wu, Chao-Feng; Sun, Wei; Li, Jing-Feng
Abstract : Rod-shaped SnS nanocrystals synthesized by solvothermal method enhances thermoelectric figure of merit due to higher carrier mobility. Abstract : Rod-shaped SnS nanocrystals were synthesized by a facile solvothermal method, which were then compacted by a cold isostatic pressing and rapid annealing process. Two-order higher carrier mobility was achieved in the corresponding bulk samples, leading to over 200% enhancement of thermoelectric figure of merit.